POLÍTICAS TERRITORIAIS E DESENVOLVIMENTO EM BURITICUPU-MA - Lacerda, Neemias Rodrigues (2014)
Analysis of the territorial politics brazilians on the territory of Maranhão, more specifically on the west of the state, where the municipality is located Buriticupu in the microregion Pindaré, whith the of objective understanding the consequences of the same conditions for current development of the municipality. For that we chose initially to do a literature review on the concepts related to the topic, such as: territory, territorial politics, development, local and then we analyze the characteristics of globalization, especially its impact on the territory and the strategies to address inequalities in the various spatial scales. Then we make a historical analysis of the territorial politics within Brazil and Maranhão. After this analysis we come to particularize the microregion Pindaré until we get the specificity of economic and social transformations produced by territorial politics for county, seeking to understand the impacts on local development. Always with a view to finding alternatives to stop the situation from low municipal development.